Performance-Based Feedback to Enhance Early Interventionist's Practice and Caregiver and Child Outcomes. (May 2019) - Coogle, Christan Grygas; Larson, Anne L.; Ottley, Jennifer R.; Root, Amy Kennedy; Bougher-Muckian, Hilary
We used a multiple-probe single-case design to determine whether there was a functional relation between peer-delivered, technology-enhanced, performance-based feedback (TEPF) and early intervention (EI) providers' use of family engagement strategies and embedded learning opportunities. Participants included three coaches, three EI providers, three caregivers, and three children receiving EI services. Results suggest that although peer-delivered, TEPF did increase some of the EI providers' practices, we did not observe a functional relation. Implications for future EI research and practice are discussed.